Samoświadomość w Stanach Zjednoczonych: historia i definicje - Pierson, Melinda R. (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Self-concept has been an important theoretical construct for children and especially for children with mild/moderate disabilities in the history of special education. This chapter will review the role that self-concept has played in the field of special education and how it has impacted children in the history of schooling in the United States. Definitional models of self-concept will be presented and analyzed in light of the impact of the social outcomes on academic/cognitive progress.